Broadening the diversity of consumers engaged in guidelines: a scoping review. Issue 6 (16th June 2022) - Synnot, Anneliese; Hill, Sophie; Jauré, Allison; Merner, Bronwen; Hill, Kelvin; Bates, Peta; Liacos, Alexandra; Turner, Tari
Abstract : Background: Guideline developers are encouraged to engage patients, carers and their representatives ('consumers') from diverse backgrounds in guideline development to produce more widely applicable guidelines. However, consumers from diverse backgrounds are infrequently included in guidelines and there is scant research to support guideline developers to do this. Objectives: To identify principles and approaches to broaden the diversity of consumers engaged in guideline development. Design: Scoping review and semi-structured interviews. Methods: We conducted comprehensive searches to March 2020 for studies, reports and guidance documents. Inclusion criteria included the terms 'consumer' (patients, carers and their representatives), 'diversity' (defined using the PROGRESS-PLUS mnemonic) and 'consumer engagement' (the active involvement of consumers at any stage of guideline development). We also conducted four interviews with consumers and guideline developers. We used descriptive synthesis to identify themes, and summarised information about implemented approaches used to broaden diversity of consumers in guidelines. Results: From 10 included documents, we identified eight themes. Themes covered general engagement concepts (Respectful partnerships; Recruitment; Expectations, process and review); specific concepts about guideline development group (GDG) engagement (Characteristics of guideline personnel; Consumers' role, characteristics and prominence; Preparing and supporting consumers); and other (non-GDG) approaches (Online methods; Consultations and research-based approaches). The most commonly included PROGRESS-PLUS categories were Disability, Race/culture/ethnicity/language, Place of residence and Other vulnerable (eg, 'disadvantaged groups'). Each theme included the views of both consumers and guideline developers. We found descriptions of 12 implemented engagement approaches to broaden diversity of consumers in guidelines. Conclusions: Relationship-building, mitigating power imbalances and meeting consumers where they are at underpin our findings. Engaging with diverse groups may require greater attention to building formal, respectful partnerships and employing inclusive engagement methods.